(untitled) (Ustozlar uchun, 2024)
ABSTRACT The article gives information about the meaning and usage of CLIL, how CLIL helps to develop the class, aim of the subject, benefits of Content language integrated learning, ways of improving speaking skills by the help of content language and integrated learning.